Psicoanálisis y víctimas. Violencia conyugal: un modelo de intervención en terreno - Giberti, Eva (Facultad de Psicología (Universidad Nacional de La Plata, Argentina), 2016)
Este trabajo pretende dar a conocer un estilo de intervención frente ala violencia conyugal que complementa y contradice las prácticashabituales mediante las cuales las víctimas deben presentarse como talesante consultorios o instituciones.Esta violencia abarca infinidad de alternativas y cada pareja seenlaza violentamente según sus motivaciones concientes e inconcientes.Como el problema ha dejado de ser privado, la elección conciente einconciente de cada pareja se desarrolla en circuitos asimétricos en losque el poder de daño físico y las predilecciones públicas y sociales jueganhabitualmente en beneficio del varón.The article describes the operation of Family Violence mobile team whichis part of Victims against Violence Program, of the Ministry of Justice and HumanRights from Argentina. The Program was founded in 2006. The staff involves120 psychologists and social workers with psychoanalytic training, 4 lawyers andpolicemen. When they receive a distress call by a victim of domestic violence, apsychoanalytic trained operator serving the toll free number 137 for 24 hoursavailable takes the call and disposes the scroll of the Team to the victims home ifthey agree. They escort the victim to complaint to court or to the hospital ifneeded or wherever she wants to go. Victims who refuses to complaint to courtconstitute 40% of the analyzed statistics. This paper is about them, analyzing thecharacteristics of these women who are contacted almost immediately after theattack. Mostly, they appear as weak-willed personalities, sleepy and powerless.It's possible to assume a dismissal of affection, in combination with disprovedand an elopement alternative as a primary defense and, in some circumstances,the chance to overcome this state of mind, according to the chronological timecoping in physical marital violence.The text proposes this activity as an application of psychoanalytic theory inthe field and by government intervention.